(untitled) (Research, Society and Development, 2021)
The public health system of a population depends on its habits, genetics and the environmental conditions. In Brazil, the economic politics is dependent on the agrobusiness, which supports the utilization of phytosanitary and/or agriculture defensives, which may be negative to the ecosystem and to the population health conditions. Those chemical compounds became accepted worldwide during the Green Revolution at the 60’s. In Brazil several agriculture defensives are sold, which controls agriculture plagues; however, they cause damages to the environment and to the non-target organisms. Then, considering the pathologies that affect people, hepatic diseases can be caused by the indiscriminate use of phytosanitary. Those pathologies are classified by the World Health Organization as one of the top 10 causes of deaths in different countries, caused by different etiologies and, among them, drugs and environmental toxicants have to be considered. As the liver pathologies establishes in a body, those anomalies may progress to a more deleterious state and even cause patient’s death. However, no effective treatment is available to the hepatic diseases. The only recommended procedure to reduce the symptoms of the disease is the change of life style, as the reduction of chemical compounds exposition. In this context, more attention to the public politics and population habits in using phytosanitary have to be considered as an important tool to control and/or revert liver diseases. Then, in this study, we present the agriculture defensives largely used in Brazil, as the adverse side effects of the chemicals to the hepatic health.